SIMULTANEOUS TWIN CUTTER TECHNIQUE FOR MACHINING THIN WALL LOW RIGIDITY PART - Izamshah, R.; Affendi, H.; Mo, J.P.T.; Kasim, M.S.; Ding, S.; Mohamad, N.; Liew, P.J.; Ali, M.A.; Sundi, S.A.; Sued, M.K. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Machining of low rigidity components such as aerospace monolithic part poses several challenges. In common manufacturing practice, the wall thickness is further reduced by peripheral milling that lead to surface dimensional error resulting in tolerance violation. The surface errors are mainly induced by the acts of cutting force, which deflect the wall on the opposite direction. Additional post machining process are generally employ to compensate with the excessive error that leads to increase the production cost. Therefore, this paper aim to solve the discrepancies with the current techniques by using a simultaneous twin cutter machining technique. An in-house twin cutter adapter has been developed to transmit the rotation from the machine spindle. A set of machining test was performed to assess the effectiveness of the propose technique. The results indicated that the deflection of the thin wall part can be neglected and hence minimize the surface errors since the same cutting forces acts on both opposite sides of the wall surface. In addition, the proposed technique able to reduce the machining time up to 50 percent as the wall structure are machined with only one single pass.